Turning metrics into reputation: Islamic green economy practices in sharia hotels - Heri Kurniawan (Nur Science Institute, 2024)
This study examines how Islamic Green Economy principles are put into practice in sharia-compliant hotels in Yogyakarta, using a penta-helix lens that brings together government, business actors, academics, media, and the community. A thematic analysis of semi-structured interviews identifies five interconnected domains: policy support and incentive gaps; operational readiness and capacity building; sharia–green alignment and assurance; market pull and reputation; and community–media engagement. While government initiatives exist (training, fiscal facilitation, and public campaigns), hotels still face unclear access pathways, limited technical know-how, and high upfront costs. Progress tends to accelerate when hotels start with low-cost operational improvements, establish baseline indicators for energy, water, and waste, and institutionalize staff training. To make sustainability claims verifiable, the study proposes a simple early-stage set of key performance indicators and a logic model linking inputs, activities, outputs, outcomes, and impacts. The analysis concludes that performance-based incentives, routine audits, and data-driven communication must move in tandem so operational gains translate into reputation and market preference, while safeguarding sharia values and environmental stewardship.